How Newark Became Newark : The Rise, Fall, and Rebirth of an American City - Tuttle, Brad R. (Book collections on Project MUSE., 2009)
For the first time in forty years, the story of one of America's most maligned cities is told in all its grit and glory. With its open-armed embrace of manufacturing, Newark, New Jersey, rode the Industrial Revolution to great prominence and wealth that lasted well into the twentieth century. In the postwar years, however, Newark experienced a perfect storm of urban troubles--political corruption, industrial abandonment, white flight, racial conflict, crime, poverty. Cities across the United States found themselves in similar predicaments, yet Newark stands out as an exceptional case. Its saga.